2019
DOI: 10.1021/acs.nanolett.9b03147
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Actuators Based on Two-Dimensional Ti3C2Tx (MXene)

Abstract: Electrochemical actuators are devices that convert electrical energy into mechanical energy via electrochemical processes. They are used in soft robotics, artificial muscles, micropumps, sensors and other fields. The design of flexible and stable electrode materials remains a major challenge. MXenes, an emerging family of 2D materials, have found applications in energy storage. Here, we report an actuator device using MXene (Ti3C2Tx) as a flexible electrode material. The electrode in 1 M H2SO4 electrolyte exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
131
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(131 citation statements)
references
References 39 publications
0
131
0
Order By: Relevance
“…While many materials, including graphene, MoS 2 , CNT, and conducting polymers have been intensively used in electrochemical actuators, MXenes are newcomers in this field. [21,26,33,45,46,79,80,120,121] The mechanism for such actuators is straightforward. For many conducting polymers, oxidative and reductive reactions occur, converting these polymers into polyions.…”
Section: Mxene Electrodes For Electrochemical Actuatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…While many materials, including graphene, MoS 2 , CNT, and conducting polymers have been intensively used in electrochemical actuators, MXenes are newcomers in this field. [21,26,33,45,46,79,80,120,121] The mechanism for such actuators is straightforward. For many conducting polymers, oxidative and reductive reactions occur, converting these polymers into polyions.…”
Section: Mxene Electrodes For Electrochemical Actuatorsmentioning
confidence: 99%
“…[21,45,46,79,120] However, if the middle layer in the trilayer structure is a polymer electrolyte membrane, the corresponding actuators can work in air (Figure 12d). [26,123] Building on the benefits of the previous study, Yu Gao et al first reported Ti 3 C 2 T x -based electrochemical actuators, both bilayer and trilayer structures (Figure 12a,d). [26] These two structures were made of Ti 3 C 2 T x flexible freestanding films, which were prepared by vacuum filtering the MXene suspension.…”
Section: Mxene Electrodes For Electrochemical Actuatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the advances in natural smart systems, numerous responsive materials that can transform dynamic and reversible shape deformations into locomotions have emerged under various external stimuli such as light, [1][2][3][4][5] humidity, [6][7][8][9][10][11][12] electric field, [13][14][15][16][17][18] organic solvents, [19][20][21] heat, [22] magnetism, [23][24][25] or a combination of multiple types of stimuli thereof. [26][27][28][29][30][31][32][33][34] Such materials exhibit the potential for applications in soft robotics, artificial muscles, and smart devices.…”
Section: Introductionmentioning
confidence: 99%